2020
DOI: 10.1111/odi.13257
|View full text |Cite
|
Sign up to set email alerts
|

Research waste‐related editorial policies of leading dental journals: Situation 2018

Abstract: Objectives To study whether specific recommendations aimed at reducing avoidable research waste were included in the author instructions of leading dental journals. Method We identified 109 peer‐reviewed and original research‐oriented dental journals that were indexed in the MEDLINE and/or SCIE database in 2018. Two authors extracted independently information regarding the endorsement of reporting guidelines (RGs), ICMJE recommendations, trial or systematic review registration, and open access (OA) and data sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…However, methodological differences and inconsistencies in definitions and reporting in primary studies did not allow the authors of that review [5] to obtain a comprehensive view of transparency practices in dental research. Consistent with the findings from the research articles, investigations of journal policies in dental journals have shown suboptimal adherence to transparency practices, for instance, by not requiring preregistration of trials [7,8].…”
Section: Introductionsupporting
confidence: 72%
“…However, methodological differences and inconsistencies in definitions and reporting in primary studies did not allow the authors of that review [5] to obtain a comprehensive view of transparency practices in dental research. Consistent with the findings from the research articles, investigations of journal policies in dental journals have shown suboptimal adherence to transparency practices, for instance, by not requiring preregistration of trials [7,8].…”
Section: Introductionsupporting
confidence: 72%
“…In addition, most inappropriate citations were interpreting non-significant results as significant (18 of 34). Such errors in citations could be replicated in further research, exert adverse influence over time (Greenberg, 2009), and lead to research waste (Almaqrami, Hua, Liu, He, 2020). Inappropriate citations could be explained by inadequate appraisal of reference articles, which lead to ignorance of available evidence, hinder scientific research progress and influence clinical decision making (Fergusson, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Among 109 peer-reviewed and original research-oriented dental journals that were indexed in the MEDLINE and/or SCIE database in 2018, a data-sharing policy was present in 32/109 (29.4%) and 2 of these had a mandatory policy. 53 This study concluded that at present data-sharing policies are not widely endorsed by dental journals. In a cross-sectional survey, 14 ICMJE-member journals and 489 ICMJE-affiliated journals that published an RCT in 2018 were evaluated with respect to data-sharing recommendations.…”
Section: Resultsmentioning
confidence: 80%